MLA 22-93 - Mineral Resource Investigation Of The Peace Rock And Deadwood River Roadless Areas, Boise And Valley Counties, Idaho - J. Douglas Causey (The National Institute for Occupational Safety and Health (NIOSH), 1993)
The Bureau of Mines conducted mineral investigations of the Peace Rock and Deadwood River roadless areas in Idaho, in 1992. Literature research was done by the Idaho Geological Survey. The study areas contain black sand placers (thorium, columbium, tantalum, titanium, uranium, and rare earth elements), gold, and molybdenum prospects. Except for unrecorded placer gold, there has been no mineral production from the areas. No mineral resources were delineated, but a multi-million tonne molybdenum resource is in the Big Pine Creek area and a 142 million m' black sand deposit is in the Stolle Meadows, Peace Valley, and Deadwood River areas. The Deadwood mine produced zinc, lead, and silver. There are six mining districts in and adjoining the areas; Warm Lake, Deadwood, Garden Valley/Lowman, Banner, Summit Flat, and Grimes Pass. Few claims, mostly placer, were active in the study area in 1992. The study areas are underlain by granitic rocks of the Idaho batholith. Most of the deposits are alluvial accumulations of heavy minerals weathered out of the Idaho batholith. Stockwork and narrow veins along shears account for the base and precious metal concentrations. Eleven prospects were examined. Workings consist of drill holes, pits and adits. Geothermal resources (hot springs) occur mainly along the Middle Fork Payette River; Vulcan Hot Springs is a designated Known Geothermal Resource Area. Sand and gravel resources are of local interest.